Carbon dioxide and nitrate co-electroreduction to urea on CuO x ZnO y - Dimitra Anastasiadou; Bianca Ligt; Yunyang He; Rim C. J. van de Poll; Jérôme F. M. Simons; Marta Costa Figueiredo (Communications Chemistry, 2023)
Abstract Urea is a commonly used nitrogen fertiliser synthesised from ammonia and carbon dioxide using thermal catalysis. This process results in high carbon dioxide emissions associated with the required amounts of ammonia. Electrocatalysis provides an alternative method to urea production with reduced carbon emissions while utilising waste products like nitrate. This manuscript reports on urea synthesis from the electroreduction of nitrate and carbon dioxide using CuOxZnOy electrodes under mild conditions. Catalysts with different ratios of CuO and ZnO, synthesised via flame spray pyrolysis, were explored for the reaction. The results revealed that all the CuOxZnOy electrocatalyst compositions produce urea, but the efficiency strongly depends on the metal ratio composition of the catalysts. The CuO50ZnO50 composition had the best performance in terms of selectivity (41% at −0.8 V vs RHE) and activity (0.27 mA/cm2 at −0.8 V vs RHE) towards urea production. Thus, this material is one of the most efficient electrocatalysts for urea production reported so far. This study systematically evaluates bimetallic catalysts with varying compositions for urea synthesis from carbon dioxide and nitrate.